2019
DOI: 10.1111/ppe.12618
|View full text |Cite
|
Sign up to set email alerts
|

The PRIDE Study: Evaluation of online methods of data collection

Abstract: Background Large birth cohort studies are extremely valuable in assessing associations between early life exposures and long‐term outcomes. Establishing new birth cohorts is challenging due to declining participation rates. Online methods of data collection may increase feasibility, but have not been evaluated thoroughly. Objective The primary objective of the ongoing PRegnancy and Infant DEvelopment (PRIDE) Study is to identify exposures during pregnancy and in early life that may affect short‐term or long‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…This study was embedded in the PRegnancy and Infant DEvelopment (PRIDE) Study [31,32], an ongoing prospective cohort study among Dutch women enrolled in early pregnancy. In short, pregnant women of 18 years of age and above, able to read and understand the Dutch language, and not more than 16 weeks pregnant were invited to participate in the PRIDE Study by their midwife or gynecologist at their rst prenatal care visit.…”
Section: General Design Pride Studymentioning
confidence: 99%
“…This study was embedded in the PRegnancy and Infant DEvelopment (PRIDE) Study [31,32], an ongoing prospective cohort study among Dutch women enrolled in early pregnancy. In short, pregnant women of 18 years of age and above, able to read and understand the Dutch language, and not more than 16 weeks pregnant were invited to participate in the PRIDE Study by their midwife or gynecologist at their rst prenatal care visit.…”
Section: General Design Pride Studymentioning
confidence: 99%
“…Furthermore, consent was asked to obtain records from prenatal care providers and pharmacists. A detailed description of the PRIDE Study can be found elsewhere [26]. For the current study, we selected all PRIDE Study participants with ongoing pregnancies who completed the first follow-up questionnaire at gestational week 17 between September 2013 and February 2018 (N=4,851).…”
Section: Study Populationmentioning
confidence: 99%
“…Despite the increasing popularity of Internet‐based studies, 1‐5 there has been limited investigation of the accuracy of self‐reported data provided by Internet‐based study participants 6 . Online questionnaires have several validity‐related advantages over paper‐based questionnaires, including built‐in internal consistency checks, pop‐ups for inadvertently skipped questions, and lower missingness 7,8 .…”
Section: Introductionmentioning
confidence: 99%